2010
DOI: 10.1007/s11666-009-9461-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase Formation and Transformation in Alumina/YSZ Nanocomposite Coating Deposited by Suspension Plasma Spray Process

Abstract: Phase formation and transformation in alumina/YSZ nanocomposite coating deposited by suspension plasma spray process Tarasi, F.; Medraj, M.; Dolatabadi, A.; Oberste-Berghaus, J.; Moreau, C.Contact us / Contactez nous: nparc.cisti@nrc-cnrc.gc.ca. Suspension Plasma Spray process was used for deposition of pseudo-eutectic composition of aluminayttria-stabilized zirconia as a potential thermal barrier coating using Mettech axial III torch. Process variables including feed and plasma parameters were altered to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…It can be appreciated that coatings were mainly crystalline with α-Al2O3 and metastable t'-ZrO2 as main phases. γ-Al2O3, usual in Al2O3 and Al2O3/YSZ coatings, was not observed due probably to two different reasons: unmelted regions kept the crystalline phases of the starting powders while an overheating of the coating together with the reheating of the coating by the subsequent deposition passes can explain the phase transformation from metastable γ-to α-Al2O3 in the melted zones [17]. Nevertheless these observed phases in the coatings are characterised by high thermal stability in a wide range of temperatures which include those of operational turbines [2], In addition, melted α-Al2O3 and t'-ZrO2 display better mechanical properties than those exhibited by the other possible crystalline phases [17].…”
Section: Sps Deposition 321 Coatings From Suspensions Up To 20 Vol%mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be appreciated that coatings were mainly crystalline with α-Al2O3 and metastable t'-ZrO2 as main phases. γ-Al2O3, usual in Al2O3 and Al2O3/YSZ coatings, was not observed due probably to two different reasons: unmelted regions kept the crystalline phases of the starting powders while an overheating of the coating together with the reheating of the coating by the subsequent deposition passes can explain the phase transformation from metastable γ-to α-Al2O3 in the melted zones [17]. Nevertheless these observed phases in the coatings are characterised by high thermal stability in a wide range of temperatures which include those of operational turbines [2], In addition, melted α-Al2O3 and t'-ZrO2 display better mechanical properties than those exhibited by the other possible crystalline phases [17].…”
Section: Sps Deposition 321 Coatings From Suspensions Up To 20 Vol%mentioning
confidence: 99%
“…However, Al2O3/ZrO2 coatings by SPS have been less addressed. Besides when SPS coatings were researched the corresponding feedstocks suspensions were too diluted (30 wt.%) for industrial scale [3,17]. For this reason, the aim of the present work is to develop a thermal barrier coating by SPS technique from aqueous Al2O3/YSZ suspensions with low power consumption by using concentrated suspensions of an eutectic composition.…”
Section: Introductionmentioning
confidence: 99%
“…Al 2 O 3 -ZrO 2 composite coatings showed higher wear resistance than pure Al 2 O 3 coatings, Tingaud et al (2010) . Tarasi et al (2010) investigated the phase formation in Al 2 O 3 -YSZ sprayed with an Axial III plasma torch. They found that the particle velocity was the key parameter to achieve stable or metastable phases.…”
Section: Wear Resistant Coatingsmentioning
confidence: 99%
“…The wide peak between 200°C and 800°C may be interpreted as the relaxation area that is a feature of amorphous materials. This relaxation involves changes in some physical properties caused by the reduction in the free volume to a closer‐to‐equilibrium condition that was not possible during rapid solidification . The sharp exothermic peak at 1018°C is related to crystallization of Yb 2 SiO 5 from amorphous phase into crystals, which is expected to spontaneously generate.…”
Section: Resultsmentioning
confidence: 99%